2000
DOI: 10.14411/eje.2000.017
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships among social parasites and their hosts in the ant tribe Tetramoriini (Hymenoptera: Formicidae)

Abstract: Abstract. The phylogenetic relationships among Palaearctic species of the ant genus Tetramorium and its social parasites of the gen era Strongylognathus, Anergates and Teleutomyrmex, were investigated electrophoretically at 21 presumptive enzyme loci. The data set comprising 33 species was analysed with distance (UPGMA, Neighbor-joining and least squares statistics) and parsimony methods (independent allele, minimum turnover and mutation coding) in order to rule out analysis-dependent effects. Several group in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 69 publications
2
39
0
Order By: Relevance
“…Second, diverse studies on Hymenoptera have indicated that social parasitism has evolved frequently, but parasitic clades are often, or even predominantly, closely related to the host species (Wilson, 1971). Although this clearly does not hold true for all Hymenoptera, it is often the case that social parasites have a sister-group relationship with their hosts (e.g., ants, Wilson, 1971;Sanetra and Buschinger, 2000;Ward, 1996;bees, Lowe and Crozier, 1997;Michener, 1974;Wilson, 1971). Our results strongly indicate that in the Acacia thrips there has been only a single origin of kleptoparasitism and inquilinism and, as far as our taxonomic representation goes, without reversions to non-parasitic habits.…”
Section: The Parasitic Suitementioning
confidence: 99%
“…Second, diverse studies on Hymenoptera have indicated that social parasitism has evolved frequently, but parasitic clades are often, or even predominantly, closely related to the host species (Wilson, 1971). Although this clearly does not hold true for all Hymenoptera, it is often the case that social parasites have a sister-group relationship with their hosts (e.g., ants, Wilson, 1971;Sanetra and Buschinger, 2000;Ward, 1996;bees, Lowe and Crozier, 1997;Michener, 1974;Wilson, 1971). Our results strongly indicate that in the Acacia thrips there has been only a single origin of kleptoparasitism and inquilinism and, as far as our taxonomic representation goes, without reversions to non-parasitic habits.…”
Section: The Parasitic Suitementioning
confidence: 99%
“…Although A. atratulus was reported previously mainly in Tetramorium caespitum (Linnaeus, 1758) and T. impurum (Förster, 1850) [4][5][6][7] nests within the Tetramorium caespitum/impurum complex, it was also recorded from Sicily (Italy) from a nontypical low altitude (300 m) in a nest of T. diomedeum Emery, 1908, which is a member of the Tetramorium ferox complex [8]. Future clarification of the complicated taxonomic composition of the Tetramorium caespitum/impurum complex will probably enlarge the number of known host ant species parasitized by A. atratulus [5].…”
Section: Introductionmentioning
confidence: 99%
“…Future clarification of the complicated taxonomic composition of the Tetramorium caespitum/impurum complex will probably enlarge the number of known host ant species parasitized by A. atratulus [5].…”
Section: Introductionmentioning
confidence: 99%
“…The suggestion is based on the observation that all inquiline ants are either closely related to their hosts (loose form of Emery's rule), or are the closest relatives to their hosts (strict form of Emery's rule) (33). Although the evidence for the loose form of Emery's rule is convincing (34), phylogeny-based studies on inquiline ants, bumblebees, and wasps have rejected the strict form of Emery's rule (35)(36)(37)(38); consequently, the studied inquilines cannot support sympatric speciation.…”
mentioning
confidence: 99%